Improving Students' Creative Thinking Skills Using Problem-Based Learning (PBL) Models Assisted by Interactive Multimedia - Lukman Nulhakim; Fajar Rizki Setiawan; Asep Saefullah (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
This study determines the improvement of students' creative thinking using problem-based learning models assisted by interactive multimedia on the concept of substance pressure. Research conducted at SMP 2 Mandalawangi, using one-sample classes, class VIII the second semester of 2017/2018 academic year, was held in May 2018. The method used is quantitative research, while the type used is quasi-experimental research, using a one-group pretest-posttest design research design. The instrument used was a test instrument for creative thinking skills in the form of elaboration questions on the concept of pressure. The analyzing data using paired sample t-test or paired sample t-test analysis to see the effect of PBL on creative thinking skills, and n-gain to see an improvement in creative thinking skills. The study gives an increase in students' creative thinking skills. The average value of 41 to 81 with an n-gain of 0.68 or an improved of 68%, which included the medium criteria. Paired sample t-test results indicate that there is an influence of the use of problem-based learning models assisted by interactive multimedia on students' creative thinking skills on the concept of substance pressure.